Pengaruh Pertumbuhan Aset dan Struktur Modal terhadap Profitabilitas Perusahaan: Studi pada Perusahaan Sektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Arshi Naisya Wahyuni; Anwar Anwar; Andi Mustika Amin; Nurman Nurman; Annisa Paramaswary Aslam (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of asset growth and capital structure on profitability in Food and Beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The data collection method used is secondary data from financial reports of Food and Beverage sub-sector companies listed on the Indonesia Stock Exchange. The population in this study was 43 companies and 16 samples were obtained using purposive sampling. The results of this study partially 1. Asset growth has a positive and insignificant effect on profitability. This is supported by the company PT Tri Banyan Tbk which experienced a decline in asset growth for 5 consecutive years. 2. Capital structure has a negative and significant effect on profitability. This shows that if the capital structure of a Food and Beverage company increases, profitability will decrease and vice versa. 3. Simultaneously, Asset growth and capital structure have a significant effect on profitability. This shows that if asset growth and capital structure increase or decrease, it will affect profitability in Food and Beverage companies.